2013
DOI: 10.1542/peds.2013-1384
|View full text |Cite
|
Sign up to set email alerts
|

Blood Cultures in the Evaluation of Uncomplicated Skin and Soft Tissue Infections

Abstract: BACKGROUND: Blood cultures are often obtained in children hospitalized with skin and soft tissue infections (SSTIs). Because little evidence exists to validate this practice, we examined the yield of blood cultures in the evaluation of immunocompetent children with SSTIs. METHODS: Medical records were reviewed for all children admitted between January 1, 2007 and December 31, 2009 after emergency department evaluation and dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 14 publications
(11 reference statements)
1
34
0
2
Order By: Relevance
“…Indeed, some studies have shown a poor performance of this tool when used in other populations. In this way, different studies performed in adult populations have identified subgroups of patients with UTI [17] or cellulitis [18] who are more likely to have concomitant bacteremia, but this finding rarely modifies the subsequent management of patients with UTIs [19], pneumonia [20,21], or cellulitis [22,23]. Other studies have validated these findings in pediatric populations, concluding that the presence of a positive BC seldom modifies the outcome of children with a UTI [24] or those with a community-acquired pneumonia [25].…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, some studies have shown a poor performance of this tool when used in other populations. In this way, different studies performed in adult populations have identified subgroups of patients with UTI [17] or cellulitis [18] who are more likely to have concomitant bacteremia, but this finding rarely modifies the subsequent management of patients with UTIs [19], pneumonia [20,21], or cellulitis [22,23]. Other studies have validated these findings in pediatric populations, concluding that the presence of a positive BC seldom modifies the outcome of children with a UTI [24] or those with a community-acquired pneumonia [25].…”
Section: Discussionmentioning
confidence: 93%
“…Consistent with prior reports, we observed a low yield of likely pathogens from blood culture analysis (2.9%) among children with SSTIs. 3,8,[12][13][14] The utility of blood culture in non-critically ill children with an SSTI is not supported by these results.…”
Section: Discussionmentioning
confidence: 85%
“…In one recent study by Malone et al, over 90% of children admitted to the hospital for SSTIs had laboratory investigation, including blood cultures, but <1% of patients had a positive culture. 8 In fact, in their study, there were no true positive blood cultures and length of stay was nearly 1 day longer if a culture had been ordered for a patient with an uncomplicated SSTI. This highlights not only the lack of utility, but also the potential harm to patients that could result from obtaining blood cultures in uncomplicated SSTIs, since a false positive blood culture often results in hospitalization or prolonged hospitalization, further laboratory testing and an extended antibiotic course.…”
Section: What Tests Should I Order When I Suspect Cellulitis?mentioning
confidence: 92%